On the Asymptotic Sum Rate of Downlink Cellular Systems With Random User Locations - Girnyk, Maksym A.; Muller, Axel; Vehkapera, Mikko; Rasmussen, Lars K.; Debbah, Merouane (IEEE wireless communications letters, 2015)
We consider a downlink cellular communication system with a multi-antenna base station (BS). A regularized zero forcing precoder is employed at the BS to manage the inter-user interference within the cell. Using methods from random matrix theory, we derive a deterministic approximation for the achievable ergodic sum rate, taking into account the randomness from both fading and random user locations. The obtained approximation describes well the behavior of finite-sized systems and enables efficient optimization of the precoder matrix.